2003
DOI: 10.1016/s0735-1097(03)00338-3
|View full text |Cite
|
Sign up to set email alerts
|

The Australian intervention randomized control of rate in atrial fibrillation trial (AIRCRAFT)

Abstract: In this trial, AVJAP for patients with mild to moderately symptomatic permanent AF did not worsen cardiac function during long-term follow-up, and quality of life was improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(53 citation statements)
references
References 16 publications
1
49
0
3
Order By: Relevance
“…A report of 350 patients from the Mayo Clinic demonstrated that in patients without underlying cardiac disease, survival at a mean follow-up of 3 years was the same as expected in the general population and as in patients treated with medications for rate control [8]. The AIRCRAFT (Australian Intervention Randomized Control of Rate in Atrial Fibrillation Trial) showed that ablation of the AV conducting system improves symptoms in patients who are unable to achieve adequate rate control with medications [9]. A meta-analysis has shown this approach to improve ventricular function, quality of life, exercise duration, and health care use with the same mortality as those treated medically [10].…”
Section: Treatment Av Node Ablation and Permanent Pacingmentioning
confidence: 87%
“…A report of 350 patients from the Mayo Clinic demonstrated that in patients without underlying cardiac disease, survival at a mean follow-up of 3 years was the same as expected in the general population and as in patients treated with medications for rate control [8]. The AIRCRAFT (Australian Intervention Randomized Control of Rate in Atrial Fibrillation Trial) showed that ablation of the AV conducting system improves symptoms in patients who are unable to achieve adequate rate control with medications [9]. A meta-analysis has shown this approach to improve ventricular function, quality of life, exercise duration, and health care use with the same mortality as those treated medically [10].…”
Section: Treatment Av Node Ablation and Permanent Pacingmentioning
confidence: 87%
“…At 1 year, patients who underwent AV junction ablation had a significantly improved quality of life, and cardiac function was not inferior to those in the pharmacologic therapy group [13]. …”
Section: Rate Controlmentioning
confidence: 90%
“…A steerable radiofrequency (RF) ablation catheter with a 4-, 5-, or 8-mm electrode tip is positioned percutaneously via the right femoral vein at the His bundle region. 4,5 To limit ablation to the AV node, and thus maintain an escape rhythm, the catheter is withdrawn slightly to record approximately equal atrial and ventricular electrogram amplitude and a small His bundle electrogram. Rarely, a left-sided, retrograde, transaortic approach is required, with ablation performed where a large His bundle electrogram is recorded on the septum just below the aortic valve.…”
Section: Methods For Av Node Modification and Ablationmentioning
confidence: 99%